Endoscopic ultrasound-guided biliary drainage for distal malignant obstruction: a systematic review and meta-analysis of randomized trials - Miller, Corey S.; Barkun, Alan N.; Martel, Myriam; Chen, Yen-I (Endoscopy International Open, 2019)
Background and study aims Endoscopic ultrasound (EUS)-guided biliary drainage (BD) is increasingly used for distal malignant biliary obstruction, yet its safety and efficacy compared to endoscopic retrograde cholangiopancreatography (ERCP) or percutaneous transhepatic biliary drainage (PTBD) remain unclear. We performed a meta-analysis to improve our understanding of the role of EUS-BD in this patient population.Methods We searched Embase, MEDLINE, CENTRAL, and ISI Web of Knowledge through September 2018 for randomized controlled trials (RCTs) comparing EUS-BD to ERCP-BD or PTBD as treatment of distal malignant biliary obstruction. Risk ratios (RRs) with 95 % confidence intervals (CIs) were combined using random effects models. The primary outcome was risk of stent/catheter dysfunction requiring reintervention.Results Of six trials identified, three (n = 222) compared EUS-BD to ERCP-BD for first-line therapy; three others (n = 132) evaluated EUS-BD versus PTBD after failed ERCP-BD. EUS-BD was associated with a decreased risk of stent/catheter dysfunction overall (RR, 0.39; 95 %CI 0.27 – 0.57) and in planned subgroup analysis when compared to ERCP (RR, 0.41; 95 %CI 0.23 – 0.74) or PTBD (RR, 0.37, 95 %CI 0.22 – 0.61). Compared to ERCP, EUS was associated with a decreased risk of post-procedure pancreatitis (RR, 0.12; 95 %CI 0.01 – 0.97). No differences were noted in technical or clinical success.Conclusions In a meta-analysis of randomized trials comparing EUS-BD to conventional biliary drainage modalities, no difference in technical or clinical success was observed. Importantly, EUS-BD was associated with decreased risks of stent/catheter dysfunction when compared to both PTBD and ERCP, and decreased post-procedure pancreatitis when compared to ERCP, suggesting the potential role for EUS-BD as an alternative first-line therapy in distal malignant biliary obstruction.